1988
DOI: 10.1128/jb.170.1.56-64.1988
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the iucD gene of the pColV-K30 aerobactin operon and topology of its product studied with phoA and lacZ gene fusions

Abstract: Gene iucD of the aerobactin operon of the Escherichia coli plasmid ColV-K30 encodes a membrane-bound enzyme synthesizing N6-hydroxylysine, the first product of the aerobactin biosynthesis pathway. The entire nucleotide sequence of the cloned iucD gene was determined, from which the primary and some aspects of the secondary structure of the encoded peptide were deduced. E. coli cells harboring multicopy plasmid pVLN12 (iucD+) hyperproduced an approximately 50-kilodalton peptide which was purified and identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 53 publications
1
54
0
Order By: Relevance
“…These codons can be read as tryptophan (W) in a supK strain (28). Shaded bases in the iucD sequence indicate the Shine-Dalgarno sequence as reported by Herrero et al (17). IucD (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…These codons can be read as tryptophan (W) in a supK strain (28). Shaded bases in the iucD sequence indicate the Shine-Dalgarno sequence as reported by Herrero et al (17). IucD (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…In a previous study, Herrero et al (17) suggested that IucD is an integral membrane protein associated with the inner membrane by at least two attachment sites. One of the membrane attachment sites appears to consist of a hydrophobic amino acid sequence resembling a leader peptide located on the amino terminus of IucD (17). The features in primary sequences of proteins determining membrane insertion are not completely elucidated (34).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both enzymes hydroxylate the primary amines of amino acid sidechains (Figure 1), and share 46 % sequence similarity. The structure of IucD has not been determined and there has been debate about the solubility and cellular localization (membrane or cytoplasm) of this enzyme (25)(26)(27)(28). Initial attempts to overexpress IucD led to insoluble protein, and hydrophobic stretches of the enzyme were identified that could serve as transmembrane helices (27).…”
Section: Discussionmentioning
confidence: 99%